A select library of the Nicene and Post-Nicene Fathers of the Christian church - Schaff, Philip; Wace, Henry; Ambrose, Saint (Edinburgh, Scotland T and T Clark, 1889)
Includes bibliographical references and indexes.
V. X contains select works and letters of St Ambrose
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600